2023
DOI: 10.1002/jev2.12300
|View full text |Cite
|
Sign up to set email alerts
|

Identification of faecal extracellular vesicles as novel biomarkers for the non‐invasive diagnosis and prognosis of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancies that is usually detected late in the clinic. The currently available diagnostic tools for CRC are either invasive or insensitive to early lesions due to the dearth of reliable biomarkers. In this study, we discovered that the extracellular vesicles (EVs) in the faeces of CRC patients can act as a potent biomarker for the non-invasive diagnosis and prognosis of CRC. This finding is based on the identification of two transmembrane proteins-CD147 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…As observed, significant difference in ECL intensity, PA signal, and color value in the CRC patients group compared to healthy humans in Figure 5G. In addition, carcinoembryonic antigen (CEA) is a clinically established serum biomarker for CRC diagnosis, 47,48 but it needs to be combined with the clinical colonoscopy test, tissue analysis, and imaging to further diagnose CRC more accurately. Therefore, the above results were compared with those of comprehensive clinical diagnosis based on CEA-ELISA, and the results remained consistent (Table S3).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…As observed, significant difference in ECL intensity, PA signal, and color value in the CRC patients group compared to healthy humans in Figure 5G. In addition, carcinoembryonic antigen (CEA) is a clinically established serum biomarker for CRC diagnosis, 47,48 but it needs to be combined with the clinical colonoscopy test, tissue analysis, and imaging to further diagnose CRC more accurately. Therefore, the above results were compared with those of comprehensive clinical diagnosis based on CEA-ELISA, and the results remained consistent (Table S3).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Recent studies focusing on EV-miRNAs have indicated their significance as non-invasive biomarkers in different malignant tumors (62). Similarly, several studies have reported the presence of small RNAs and their potential application for NB prognosis.…”
Section: Nb-evs In Nb Diagnosis and Prognosismentioning
confidence: 98%
“…EVs derived from adipocytes and adipose-endothelial cells were found to induce proliferation, migration and invasion of the recipient prostate cancer cells, thereby promoting metastasis in prostate cancer (64, 65). While CAFs were found to support the surrounding tumor cells by transferring tumor-supportive signals via EVs, thereby contributing to tumor growth and metastasis in several cancer types (62,(66)(67)(68). In addition, endothelial cell derived-EVs were shown to affect macrophages, by converting them to a M2-like phenotype thereby inducing an immunosuppressive environment and aiding in cancer progression (69).…”
Section: Tumor Derived Evsmentioning
confidence: 99%
“…In this context, we found only one study that has looked for potential CRC biomarkers in fecal EVs (fEVs). Zhang et al, 2023 showed, by Western blot, immunogold transmission electron microscopy, immunofluorescence, and ELISA, that the levels of the proteins CD147 and cell surface A33 antigen on fEVs were higher in CRC patients, compared to healthy donors, with no significant variation across the different stages of CRC [95].…”
Section: Proteomic Analysis Of Stool In Crcmentioning
confidence: 99%